2016
DOI: 10.1002/app.44157
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and crystallization behavior of PCL/SAN blends containing nanosilica with different surface properties

Abstract: Morphology and crystallization behavior of poly(E-caprolactone) (PCL) in its 80/20 blends with poly(styrene-co-acrylonitrile) (SAN) containing hydrophobic or hydrophilic nanosilica was investigated. It was found that hydrophilic nanosilica displayed a more significant refinement effect on co-continuous morphology of PCL/SAN blends than hydrophobic nanosilica for its selective distribution within the PCL matrix but closer to the two-phase interface. Ring-banded spherulites were observed in both kinds of nanosil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…These transitions are very different to those in classical copolymer compatibilised polymer blends. Qian et al [34] reported the morphology and crystallization behaviour of poly(Ecaprolactone) in its 80/20 blends with poly(styrene-co-acrylonitrile) containing hydrophobic or hydrophilic nanosilica particles. It was found that hydrophilic nanosilica displayed a more significant effect in the morphology of the blends than hydrophobic nanosilica.…”
Section: Polymer-oil and Polymer-polymer Interfacesmentioning
confidence: 99%
“…These transitions are very different to those in classical copolymer compatibilised polymer blends. Qian et al [34] reported the morphology and crystallization behaviour of poly(Ecaprolactone) in its 80/20 blends with poly(styrene-co-acrylonitrile) containing hydrophobic or hydrophilic nanosilica particles. It was found that hydrophilic nanosilica displayed a more significant effect in the morphology of the blends than hydrophobic nanosilica.…”
Section: Polymer-oil and Polymer-polymer Interfacesmentioning
confidence: 99%
“…In bulk film (>3 μm), neat PCL forms ringless spherulite during melt crystallization; however, clear ring bands are obtained with physical blends. [54][55][56][57][58][59][60] The bulk thickness has freedom to generate a crystal nucleus in the top, center, and bottom layers in the 360°radius. [34,[61][62][63][64] At the same time, in thin film, crystallization occurs in the geometrical confinement; a lamella grows by sluggish attachment of polymeric chains in growth front.…”
Section: Introductionmentioning
confidence: 99%
“…[64,65] When the film thickness drops lesser than a lamella size, the slow diffusion of chains restricted the crystallization. [65] In crystalline/amorphous polymer blends, [54][55][56][57][58][59][60] phase separation accumulation of amorphous diluents in the growth front alters the crystal orientation in the spherulite. [66,67] Moreover, the addition of amorphous diluents of poly(phenyl methacrylate) (PPhMA) or poly(benzyl methacrylate) to PCL produces ring bands at lower crystallization temperatures (T c ).…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL) and its blends are widely used in various medical applications including artificial skin, resorbable prostheses, chemotherapy, tissue engineering, and pharmaceutical formulations due to its biocompatibility, biodegradability, and nontoxicity (FDA approved). PCL is a biodegradable, hydrophilic, crystallizable polymer with a crystalline structure similar to that of polyethylene made of an orthorhombic unit cell and extended zigzag conformation . PCL is reported to be miscible with a large range of chlorinated polymers due to dipole–dipole interactions between carbonyl and C–Cl groups. ,, Blends of PCL with a hydrophilic, nontoxic, and biodegradable polymer such as poly­(ethylene glycol) (PEG) are expected to improve their biodegradation and hydrophobic properties, thus making them suitable for short-term drug delivery. , They form immiscible blends, as demonstrated by Qui et al by phase contrast miscroscopy …”
Section: Introductionmentioning
confidence: 99%